Practitioner and researcher collaboration through a student Master’s paper - White, Hollie; Chan, Janice; Cairns, Amy (2020)
Australian library practitioners perceive that research performed by library researchers is often irrelevant and unaligned to what they need. Practitioner and researcher collaboration is one solution to address this issue. This paper explores a collaboration between an academic library and a library and information studies department that focuses on practitioner-relevant research conducted by a master’s student pursuing a Degree by Coursework. Using autoethnographic and critical reflective practice techniques, three different perspectives – an academic librarian, a library school researcher, and a master by coursework student – on the research collaboration will be presented and explored.